2023
DOI: 10.1039/d3ta00872j
|View full text |Cite
|
Sign up to set email alerts
|

Rational strategy to enhance the thermal stability of solar cell performance using a photocrosslinkable conjugated polymer

Abstract: In addition to the power conversion efficiency (PCE) of polymer solar cells (PSCs), long-term stability is a critical requirement. In this study, a crosslinkable PM6-based polymer donor, PM6-X30, was developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The optimal sample exhibited a PCE of 11.20%, which was achieved with 2.5 wt % BABP and 8 min of UV treatment. The UV treatment time was reduced to mitigate prolonged UV irradiation, which can induce cross-linking reactions, accompanied by the degradation and photobleaching of the PM6 material . A comparative analysis (Table S1) revealed that with 2 wt % BABP, PCE values of 10.24 and 8.71% were recorded for 8 and 15 min of UV treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The optimal sample exhibited a PCE of 11.20%, which was achieved with 2.5 wt % BABP and 8 min of UV treatment. The UV treatment time was reduced to mitigate prolonged UV irradiation, which can induce cross-linking reactions, accompanied by the degradation and photobleaching of the PM6 material . A comparative analysis (Table S1) revealed that with 2 wt % BABP, PCE values of 10.24 and 8.71% were recorded for 8 and 15 min of UV treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, photo-cross-linking was performed by exposing the PM6 films with BABP to UV light for less than 15 min. This is because prolonged irradiation under such harsh conditions can induce cross-linking reactions, accompanied by degradation and photobleaching of the organic materials …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations